MEKANISME KEGAGALAN PAHAT PADA PROSES MILLING AKIBAT ALIRAN SERPIHAN PEMESINAN KECEPATAN TINGGI AISI 4140 - Saputra, Aswin; Yunus, Surya Murni (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
The mechanism of tool failure is the way to wear wear damage on the tool. This study aims to investigate the mechanism of tool wear / tool wear (Vb) which is useful to provide information on the wear mechanism of the tool in a high-speed, dry machining process with a HSS Cobalt M42 tool used for machining milling of AISI 4140 steel material. the cutting speed (v) differs above 200 m / min, the cutting depth (a) = 0.5 mm, the feeding motion (f) = 0.5 mm / min and the main cutting angle of the tool (Kr) = 90 ° at the rate condition high speed cutting. From the results of the study the mechanism of tool failure that occurs is side wear. Where the highest wear wear occurs in conditions v = 755 m / min, f = 0.5 mm / min, a = 0.5 mm, with flake thickness (hc) = 0.88 mm and flake flow velocity (Vc) = 431.42 m / where the value of Vb = 0.325 mm. The wear mechanism that occurs due to the flow of debris that moves upward touches the cutting edge of the tool with the shape of the broken debris.